Component selection strategy for an anthropomorphic robot - ., Md. Akhtaruzzaman; Shafie, Amir Akramin; Muhammad , Mahbubur Rashid (2011)
Bipedal systems have an improved mobility to navigate on the rough and hazardous terrains, inclined surface, steep stairs and obstacle environs. The distribution and position of internal Degree of Freedom (DoF) in anthropoid kinematic chain delineates the common kinematic propensity of a walking biped robot. Fundamentally the internal DoF of the lour torso are naturally reorganized at hip, knee, ankle and toe type articulations. The investigation represents the panoptic view in selecting the various components to design and develop a anthropomorphic platform. An elaborate and systematic plan to assign the DoF and select the required torque of each actuator is cogitated in this paper. The writings also represent the possible architecture of control mechanism of the system which is one of the major parts of the android.